ANALISIS PENGARUH KINERJA KEUANGAN TERHADAP RETURN SAHAM - Wicaksono, Maheranto (Jurnal Ilmiah Mahasiswa FEB, 2016)
This study aims to analyze the financial performance of companies on stock returns. Financial performance is represented by variables Return on assests ratio (ROA), Return on Equity (ROE), Current Ratio (CR), Debt To Total Assets (DTA), Net Profit Margin (NPM) and Earning Per Share (EPS). This  type  of  research  is  an  explanatory  research  (explanation). Total sample of 50 companies with 200 entries in the manufacturing sector companies listed on the Indonesia Stock Exchange. The method of analysis used in this study is multiple regression method. The results showed that the Return on Assests Ratio (ROA), Return on Equity (ROE), Current  Ratio  (CR), Debt  To  Total  Assets  (DTA),  Net  Profit Margin  (NPM) and  Earning Per Share  (EPS) simultaneously affect  the  stock returns.  Partial  test  shows  that  the  variable  Return  on  Assests  Ratio  (ROA), Return on Equity (ROE), Net Profit Margin (NPM) and Earning Per Share (EPS) significant influence, while the variable Debt To Total Assets (DTA) and Current Ratio is not significant effect on stock returns. Of the variables mentioned above, Return on Equity is the dominant variable striving to stock return.   Keywords:     Financial   Performance:   Return   on   Assests   Ratio   (ROA), Return On Equity (ROE), Current Ratio (CR), Debt To Total Asset (DTA), Net Profit Margin (NPM), Earning Per Share (EPS) and Return stock